Genome-wide association analysis suggests novel loci underlying thyroid antibodies in Hashimoto’s thyroiditis - Brčić, Luka; Barić, Ana; Gračan, Sanda; Torlak, Vesela; Brekalo, Marko; Škrabić, Veselin; Zemunik, Tatijana; Barbalić, Maja; Punda, Ante; Boraska Perica, Vesna (Scientific reports, 2019)
Thyroid antibodies against thyroglobulin (TgAb) and thyroid peroxidase (TPOAb) are key markers of Hashimoto’s thyroiditis (HT), the most common autoimmune thyroid disorder. Genetic determinants of thyroid antibodies are still poorly known, especially as they were not studied in patients with thyroid diseases. We performed the first genome-wide association analysis of thyroid antibodies in 430 HT patients that may be considered as population extremes for thyroid antibodies distribution. We detected two suggestively associated genetic variants with TgAb, rs6972286 close to ANKRD7 and LSM8 (P = 2.34 × 10 −7 ) and rs756763 inside CA10 (P = 6.05 × 10 −7 ), and one with TPOAb, rs12507813 positioned between TRIM61 and TRIM60 (P = 4.95 × 10 −7 ). Bivariate analysis resulted with three suggestively associated genetic variants that predispose to both antibodies: rs13190616 inside RP11-138J23.1 (P = 2.01 × 10 −6 ), rs561030786 close to DUBR (P = 7.33 × 10 −6 ) and rs12713034 inside FSHR (P = 7.66 × 10 −6 ). All identified genomic regions have a substantial literature record of involvement with female-related traits, immune-mediated diseases and personality traits that are all characterized by increased thyroid antibody levels. Our findings demonstrate the existence of genetic overlap between thyroid autoimmunity in HT and different non-thyroid diseases characterized by the presence of thyroid antibodies. We also suggest that genetic variants that regulate antibody levels may differ between HT patients and individuals with normal thyroid function.